Heterologous Expression of Laccase From Lentinula edodes in Pichia pastoris and Its Application in Degrading Rape Straw - Liu, Chanjuan; Zhang, Wenjing; Qu, Mingren; Pan, Ke; Zhao, Xianghui (Frontiers in Microbiology, 2020)
Rape straw cannot be efficiently degraded and utilized by ruminants due to its severe lignification and complex cross-linked structure between fiber and lignin. The laccases can catalyze the inter-unit bond cleavage in lignin substrates. Therefore, this study investigated the recombinant laccase from Lentinula edodes (LeLac) and its application in degrading rape straw. The LeLac was expressed using Pichia pastoris. It had the maximum activity at 60 °C and pH 3.0 using ABTS as substrate and at 50 °C and pH 4.0 using o-tolidine as substrate. The LeLac exhibited preferential oxidation of ABTS and featured resistance to high temperature, but relatively poor thermal stability. The LeLac activity could be strengthened by Cu2+ in dose-dependent manners. The LeLac could tolerate 15% of ethanol and methanol. The optimal pH for the lignin degradation of rape straw acid detergent fiber (ADF) by LeLac was 4.0. The LeLac could improve the cellulose enzymolysis of rape straw ADF by degrading its lignin. Relatively fewer lignin but more soluble phenols from original rape straw were removed by LeLac. The enhancement of enzymatic hydrolysis in original rape straw should be a combined result of polyphenols removal and lignin degradation caused by LeLac. This study demonstrated that the LeLac could improve the utilization of rape straw by degrading its lignin, meanwhile it’s worth noting that removing the soluble phenols by LeLac might also play an important role.